The socioeconomic level of public school students and the conditions for the provision of education in the Brazilian municipalities - Thiago Alves; Maria Aparecida Gouvêa; Adriana Backx Noronha Viana (Arizona State University, 2012)
The purpose of this article is to analyze the socioeconomic background of elementary school students from public schools in the Brazilian municipalities, through a synthetic measure, the Student Socioeconomic Index of the Municipalities (ISE-M). It also aims to analyze the achievement in educational assessments and the conditions for the provision of education in the municipalities. The ISE-M was generated through factor analysis with the use of data from the contextual questionnaire of Prova Brasil 2007 (2007 Brazil Test) held with approximately 4.1 million students in 5,553 municipalities. The results ratified the association between the socioeconomic level of students and the educational outputs observed in other studies. In addition, they showed that there is a relationship between the socioeconomic status and the educational infrastructure available in the municipalities, because there is evidence that the conditions for the provision of education are lower in places that have a higher proportion of socioeconomically disadvantaged students.